Manajemen Risiko Metode Pembayaran Cash On Delivery Shopee E-Commerce - Rina Puji Rahayu; Aji Damanuri (Journal of Economics, Law, and Humanities, 2023)
Cash On Delivery is a payment method provided to customers by online marketplace companies. However, various problems arose with continued shopping promotions with the Cash On Delivery payment method. The research was conducted using a descriptive method with a qualitative approach based on data sources from literature and observation. This study aims to provide an overview of the risks regarding the Cash On Delivery payment method from the point of view of online sellers and to analyze Shopee's policy on handling the risks associated with the Cash On Delivery payment method. The results showed that the factors behind unilateral cancellation of transactions using Cash On Delivery payments were caused by the buyer changing his mind, the buyer not having the money to pay, the buyer accidentally ordering or clicking checkout, the buyer could not be contacted (no response), and the order was not fit/damaged. The risks faced by sellers from this method are loss of human resources, risk of financial loss, loss of time, and risk of decreased store performance. Shopee has implemented several policies to minimize risk, but Shopee must improve the pay on the Delivery feature. Given that the unilateral cancellation of the customer is very detrimental to the seller.